2010
DOI: 10.1103/physreve.81.011408
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium fluctuation-dissipation relations of interacting Brownian particles driven by shear

Abstract: We present a detailed analysis of the fluctuation dissipation theorem (FDT) close to the glass transition in colloidal suspensions under steady shear using mode coupling approximations. Starting point is the manyparticle Smoluchowski equation. Under shear, detailed balance is broken and the response functions in the stationary state are smaller at long times than estimated from the equilibrium FDT. An asymptotically constant relation connects response and fluctuations during the shear driven decay, restoring … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
25
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 75 publications
(218 reference statements)
9
25
2
Order By: Relevance
“…This lends further support to the earlier discussion of nonequilibrium fluctuationdissipation ratios and Einstein relations within MCT and its schematic models, as the equivalent approximations have been used there [11,15,32].…”
Section: Discussionsupporting
confidence: 80%
“…This lends further support to the earlier discussion of nonequilibrium fluctuationdissipation ratios and Einstein relations within MCT and its schematic models, as the equivalent approximations have been used there [11,15,32].…”
Section: Discussionsupporting
confidence: 80%
“…The relationship between the response and correlation functions is of great interest and importance [1][2][3][4][5][6][13][14][15][16][17][18][19][20][21]. If we use the shear moduli G …”
Section: Violation Of Fluctuation-dissipation Theoremmentioning
confidence: 99%
“…Furthermore, in glassy systems, including supercooled liquids, it has been suggested that the equilibrium form of the FDT holds at long times with the temperature T replaced by an effective temperature T eff [13], which indicates that T eff can be used to relate the response and correlation functions. Several numerical and theoretical works have examined the validity and the role of the effective temperature in such situations [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…There has been a lot of interest in recent years in the dynamics of interacting Brownian particles [9][10][11][12][13][14]. The reason for this interest is twofold [15].…”
mentioning
confidence: 99%
“…Second, interacting Brownian particles constitute the simplest model system, on which one can test techniques and approximations of nonequilibrium statistical mechanics. Many-particle systems may exhibit some features not found in the single-particle counterparts, such as phase transitions, spontaneous ratchet effects, and negative mobility [9][10][11][12][13][14]. The interacting Brownian ratchets been proposed for a variety of applications, including molecular motors [2], friction [16], diffusion of dimers on surfaces [17], diffusion of colloidal particles [18], DNA translocation through a nanopore [19], charge density waves [20], and arrays of Josephson junctions [21].…”
mentioning
confidence: 99%